On the Two Wills: Augustine against Agonism toward Peace - Clemmons, Thomas R. (Editorial Uniagustiniana, 2019)
This essay examines Augustine's critique of a hermeneutic of agonism in relation to his consideration of the Manichaean notion of the two souls, as well as his discussion of the two wills in the Confessions. The essay treats these dimensions as found in his early works De Genesi contra Manichaeos and De vera religione, as well as his work De duabus animabus, and lastly the Confessions. Augustine's recurring treatment of the two souls is bound with his critique of agonism. It is also linked with his own deepening understanding of the hermeneutical consequence of the luminous self and the weight of consuetudo. In this context Augustine's articulation of peace as an openness to God and others comes to fruition. Peace, for Augustine, is not the assertion of one's distinctive luminosity or even the resolve of a secure self at odds with the world in which it finds itself. Rather, peace is found in the realization that one is made open to difference, to a concord that does not require struggle and agony, and in fact precludes the consumption or erasure of this difference